Revealing the Existence of Diverse Strategies for Phosphorus Solubilization and Acquisition in Plant-Growth Promoting Streptomyces misionensis SwB1 - Yunzhu Chen; Zhuangzhuang Gao; Yan Yang; Qiang Liu; Lijuan Jiang; Jingzhen Chen; Xiao Zhou; Luhong Zhang; Yuena Ji; Jia Tu; Zhihong Xiao; Peiwang Li; et al. (Microorganisms)
Phosphorus deficiency poses a significant challenge to plant growth and development, particularly in red soil. To alleviate this limitation, phosphorus-solubilizing bacteria (PSB) play a crucial role by converting insoluble phosphates present in the soil into soluble forms that are accessible to plants. Cornus wilsoniana Wangerin is a representative oil crop cultivated in red soil, holding a prominent position within China’s forestry economic system. Consequently, it is essential to develop highly stable microbial phosphorus enhancement strategies to manage agricultural phosphorus in red soil regions, thereby maintaining the available phosphorus content necessary for the production of C. wilsoniana. In this study, the application of Streptomyces misionensis SwB1 bacterial suspension to the rhizosphere of C. wilsoniana significantly increased the content of various phosphorus fractions (H2O-P, NaHCO3-P, NaOH-P, HCl-P) in red soil, with NaHCO3-P content increasing by 4.97 times and NaOH-P content by 3.87 times. Additionally, the genome of S. misionensis SwB1 contains 25 phosphorus-solubilizing genes, 13 nitrogen-fixing genes, 17 siderophore production genes, and 11 indole-3-acetic acid (IAA) production genes, indicating its potential for enhancing nutrient availability. Comparative genomic analysis of 15 strains belonging to five species of Streptomyces revealed that S. misionensis SwB1 possesses an extensive genetic repertoire and complete gene clusters associated with phosphorus solubilization. Furthermore, five phosphorus solubilization pathways of S. misionensis SwB1 were summarized: the Pst system, Pit system, siderophore transport, phosphatase synthesis, and organic acid synthesis. Ultimately, the inoculation of S. misionensis SwB1 significantly enhanced the growth and biomass accumulation of C. wilsoniana at the seedling stage, evidenced by an increase in fresh weight by 81.44%, a rise in net photosynthetic rate by 18.51%, and a surge in the number of root tips by 36.24%. Taken together, our findings support a sophisticated multi-pathway bacteria phosphorus solubilization approach and identified a highly efficient phosphorus-solubilizing strain, S. misionensis SwB1, which has the potential to become a microbial fertilizer.